A Screen for Conditional Growth Suppressor Genes Identifies the Drosophila Homolog of HD-PTP as a Regulator of the Oncoprotein Yorkie. - Gilbert, M.M.; Tipping, M.; Veraksa, A.; Moberg, K.H. (Developmental Cell, 2011)
Mammalian cancers depend on "multiple hits," some of which promote growth and some of which block apoptosis. We screened for mutations that require a synergistic block in apoptosis to promote tissue overgrowth and identified myopic (mop), the Drosophila homolog of the candidate tumor-suppressor and endosomal regulator His-domain protein tyrosine phosphatase (HD-PTP). We find that Myopic regulates the Salvador/Warts/Hippo (SWH) tumor suppressor pathway: Myopic PPxY motifs bind conserved residues in the WW domains of the transcriptional coactivator Yorkie, and Myopic colocalizes with Yorkie at endosomes. Myopic controls Yorkie endosomal association and protein levels, ultimately influencing expression of some Yorkie target genes. However, the antiapoptotic gene diap1 is not affected, which may explain the conditional nature of the myopic growth phenotype. These data establish Myopic as a Yorkie regulator and implicate Myopic-dependent association of Yorkie with endosomal compartments as a regulatory step in nuclear outputs of the SWH pathway.